Analisis Perhitungan Kebutuhan Tenaga Kerja Petugas Rekam Medis Kiara Berdasarkan Teori WISN di RSUPN Dr. Cipto Mangunkusumo - Adlien Fadillah; Atma Deharja; Jalahan Pandiangan (Politeknik Negeri Jember, 2020)
The increasing number of patients required higher of medical record services. It can affect on workload officers. It is known that every day there are 350-400 patients with 20 new patients who come for treatment at RSCM Kiara. One service achievement of 32% in January 2020 with priority KPI (Key Performance Indicator) is the provision of medical record files withput patient agreement up to poluclinic < 30 minutes, of the percentage should be 100%. Based on the pre survey at RSCM showed towards 6 Kiara RSUPN Dr. Cipto Mangunkusumo medical record officers, it can be inferred that the officers having a double job at the same time. The high workload that the officers experienced is a side effect from not having enough numbers of officers. It implies that the officers could have several problems, including physical fatigue. The purpose of this study was to determine the number of labor requirements based on WISN theory for the assembling and filling officer of Kiara RSUPN Dr. Cipto Mangunkusumo. This research using a qualitative method with 6 respondents. Based on the workload calculation using the WISN method, it is known that the number of workers needed in the assembling unit is 2 people and in the filing unit is 15 people. With the results of the calculations of labor needs based on WISN theory, it can be used as an effort to plan the addition of officers numbers in order to improve the quality of hospital services according to the existing workload.